Profissionalismo: percepção de estudantes do curso de medicina da Universidade Federal de Alagoas - Campus de Arapiraca - Menezes, Marcelo Calazans Duarte de (2023)
The technological advances in science that occurred in the last century have improved the accuracy of diagnostics and treatment in health; on the other hand, it robotized the relationships between doctors and their patients. From this perspective, there is an urgent need to debate the construction of a new model for medical professionalism, which seeks to humanize this complex relationship. Within this new concept of professionalism, medical schools need to be aware that topics such as bioethics, communication, patient autonomy and social justice are included in the teaching and learning process of students. Problematizing the concept of medical professionalism as a professor of the Medicine course at the Federal University of Alagoas (UFAL) - Arapiraca Campus and a master's student in the Postgraduate Program in Clinical Management (PPGGC), the following research question was reached: How does the student body of the Medicine course at UFAL - Arapiraca Campus perceive, throughout their undergraduate studies, the development of their competence profile in relation to professionalism? Therefore, the general objective of the present study is to understand the perception of the student body at UFAL - Arapiraca Campus with regard to the development of the competence profile in relation to professionalism throughout the medical degree. The specific objectives are: to understand and discuss the principles and conceptions about professionalism from the student perspective; and evoke learning opportunities about professionalism experienced during the medical course. This is a cross-sectional and exploratory case study in which a qualitative research approach was used. An online focus group was held with students about to enter the final year of the Medicine course. The material was analyzed according to the Meaning Interpretation Method. Regarding ethical aspects, all students were invited and informed about the possible risks of the research, and the Free and Consent Form (TCLE) was presented. The reinterpretation of contextualized speeches gave rise to categories of analysis that have an ingrained dialogue with professionalism, namely: Communication and Humanization; Professionalism and Comprehensiveness of care; and Hidden Curriculum. It was noticeable that several attributes related to professionalism are being incorporated by students throughout their degree, such as: responsibility, self-reflection, respect for patients, ethics, teamwork and social responsibility. However, the hidden curriculum appeared as an obstacle to the development of professionalism attributes. In order to mitigate the harmful effects of the hidden curriculum, a set of actions derived from this research was developed, which can be characterized as a Technical Product: insertion of the term medical professionalism in menus of educational modules related to medical practice that make up the new version of the Course PPC, published in August 2023; and the offer of an Active Learning Methodologies course, starting in August 2023, for 80% of the course's teachers, with the aim of improving the teaching-learning process for the development of attributes of medical professionalism.